Authentic Leadership Model: Theoretical conception and validity evidences of the Authentic Leaderhip Questionnaire (ALQ) for Brazil - Cervo, Clarissa Socal (2018)
The Authentic Leadership Model stands out among positive theories of leadership. The most frequently used instrument to determine the leader’s authenticity is the Authentic Leadership Questionnaire (ALQ). Brazil lacks studies about the validity of this measure. The aim of this research is to present evidence of validity (ALQ) for the Brazilian work context. Leaders (N = 437) and followers (N = 1329) belonging to organizations in the South of the country participated in this research. The ALQ was applied in its self and hetero-assessment versions. Confirmatory Factor Analysis indicates the presence of the four factors of the Authentic Leadership model, and the ALQ shows reliability and validity for the Brazilian samples studied. The private nature influences the perception of leadership authenticity, but the results do not confirm the influence of socio-demographic variables (age, gender, education and salary) or the organization’s size. The limitations of the study are discussed together with suggestions for future research.